Geographic variations of song and rain calls of the Chaffinch across the ranges of three subspecies - Ivanitskii, Vladimir; Samsonova, Irina; Marova, Irina (Ornis Hungarica, 2023)
Abstract We analyze the variability of the Chaffinch’s (Fringilla coelebs) song and rain calls in 20 populations localized along a transect of about 3,000 km, crossing the territory of European Russia between the White Sea, Crimean Peninsula and the Caucasus Mountains. Three subspecies of Chaffinch inhabit this area: European (F. c. coelebs) , Caucasian (F. c. caucasicus) , and Crimean (F. c. solomkoi) . The results of cluster analysis based on song show that the populations of Crimea and southeastern Dagestan stand out the most. All other populations fall clearly into two clusters corresponding to the European and Caucasian subspecies. In most of the European subspecies vast range in Russia, the “buzzing” dialect of the rain call is widespread. Only in the extreme northwest of Russia, it is replaced by a whistling dialect. In most of the Caucasus and in the Ciscaucasia, Chaffinches also emit exclusively whistling sounds, but of a completely different structure. In the Western Caucasus, Chaffinches perform also a whistling call having a unique two-syllable structure. The Crimean peninsula is inhabited by whistling Chaffinches as well, although the frequency modulation of its call is different from that of Caucasian subspecies. We discuss the spatial distribution of song types and of rain calls dialects within the ranges of subspecies and in the contact zones between them.